2016
DOI: 10.4269/ajtmh.15-0537
|View full text |Cite
|
Sign up to set email alerts
|

Dengue Patients with Early Hemorrhagic Manifestations Lose Coordinate Expression of the Anti-Inflammatory Cytokine IL-10 with the Inflammatory Cytokines IL-6 and IL-8

Abstract: Abstract. Dengue is responsible for a wide range of clinical manifestations, ranging from asymptomatic infections to severe cases. The alteration of cytokine levels correlated with clinical characteristics can help determine prognostic markers of the disease and the identification of targets for immunotherapy. We measured the viral load, serotype, and cytokine levels of 212 serum samples from patients with acute dengue infection during days 1-4 after the onset of symptoms. The patients were classified as eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…IL-6 as well IL-8 is associated with the acute-phase response and represents key inflammatory signals to induce an effective immune response as they are responsible for the activation of cellular components of the innate response and coordinate the T-lymphocyte proliferation. Nevertheless, during dengue infection, high levels of IL-6 and IL-8 are associated with severe/hemorrhagic infections [ 23 , 24 ], suggesting that an unbalanced inflammatory response may participate to the pathogenesis of the disease. Of note, it has been recently reported in dengue infection that a coordinate balance between proinflammatory and regulatory signals represent the key for a protective immune response [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IL-6 as well IL-8 is associated with the acute-phase response and represents key inflammatory signals to induce an effective immune response as they are responsible for the activation of cellular components of the innate response and coordinate the T-lymphocyte proliferation. Nevertheless, during dengue infection, high levels of IL-6 and IL-8 are associated with severe/hemorrhagic infections [ 23 , 24 ], suggesting that an unbalanced inflammatory response may participate to the pathogenesis of the disease. Of note, it has been recently reported in dengue infection that a coordinate balance between proinflammatory and regulatory signals represent the key for a protective immune response [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, during dengue infection, high levels of IL-6 and IL-8 are associated with severe/hemorrhagic infections [ 23 , 24 ], suggesting that an unbalanced inflammatory response may participate to the pathogenesis of the disease. Of note, it has been recently reported in dengue infection that a coordinate balance between proinflammatory and regulatory signals represent the key for a protective immune response [ 24 ]. On the other side, IL-9 is a cytokine produced primarily by CD4+ Th9 cells and is generally reported to mediate allergic and autoimmune diseases [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting study concluded that polymorphisms associated with low IL10 production can increase the chances for severe dengue presentation 19 . Importantly, there is evidence showing loss of coordinate regulation between the anti‐inflammatory cytokine IL10 and the inflammatory cytokines IL6 and IL8 in patients with more severe disease 20 …”
Section: Introductionmentioning
confidence: 99%
“…In line with this assumption, a report in the literature showed that the overexpression of pro-inflammatory cytokines has been suggested to cause an inhibitory influence on regulatory cells [59]. Another recent report revealed that, in fact, a disturbance in the balance between inflammatory (IL-6 and IL-8) and anti-inflammatory (IL-10) cytokines, would characterize possible mechanisms related to the occurrence of hemorrhagic manifestations in dengue [60]. Additionally, IL-10 has also been interpreted as a marker of disease progression in severe dengue cases [61].…”
Section: Discussionmentioning
confidence: 94%